2020
DOI: 10.3389/fpsyg.2020.00626
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Person-Centered Examination of Teachers’ Workplace Demands and Resources: Links With Work-Related Well-Being

Abstract: Teachers' healthy and effective functioning at work is impacted by the demands they face and the resources they can access. In this study, person-centered analysis was adopted to identify distinct teacher profiles of demands and resources. We investigated teachers' experiences of two job demands (barriers to professional development and disruptive student behavior), two job resources (teacher collaboration and input in decision-making), and one personal resource (self-efficacy for teaching). Using data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 65 publications
(139 reference statements)
3
81
1
1
Order By: Relevance
“…For the single-level LPA conducted at the student-level (Level 1; L1), we tested a range of solutions involving 1 through 9 profiles. Following Collie et al ( 2020 ), variances and means were free to differ across profiles and indicator variables; models were estimated using at least 10,000 random start values, with 100 iterations and 1,000 final stage optimizations; and we confirmed that the best log-likelihood value was replicated for each model. Numerous indices were used to assess model fit: for the Consistent Akaike Information Criteria (CAIC), Akaike Information Criteria (AIC), Bayesian Information Criteria (BIC), and sample-size-adjusted Bayesian Information Criteria (SSA-BIC), smaller values reflect better fit.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…For the single-level LPA conducted at the student-level (Level 1; L1), we tested a range of solutions involving 1 through 9 profiles. Following Collie et al ( 2020 ), variances and means were free to differ across profiles and indicator variables; models were estimated using at least 10,000 random start values, with 100 iterations and 1,000 final stage optimizations; and we confirmed that the best log-likelihood value was replicated for each model. Numerous indices were used to assess model fit: for the Consistent Akaike Information Criteria (CAIC), Akaike Information Criteria (AIC), Bayesian Information Criteria (BIC), and sample-size-adjusted Bayesian Information Criteria (SSA-BIC), smaller values reflect better fit.…”
Section: Discussionsupporting
confidence: 59%
“…Multi-level LPA solutions (1–9 classroom-level profiles) were assessed. Following Collie et al ( 2020 ), each model was estimated using at least 10,000 random start values, 100 iterations, and 1,000 final stage optimizations; replication of the best log-likelihood value was sought for each model; and the best model was selected using the same criteria as the single-level LPA (phase 1), except the p LMR, which is not available for multi-level LPA. After identifying the network of classroom-level profiles (the classroom-level within-network validity aspect), we then examined the network of L2 outcomes (classroom-average persistence, disengagement, and achievement) as a function of profile membership by adding classroom-average outcome variables (using the M plus cluster mean approach) to the final best-fitting model (the classroom-level between-network validity aspect).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…n los últimos años ha cobrado relevancia el estudio de las capacidades y las fortalezas que pueden mejorar el rendimiento del personal laboral en distintos ámbitos laborales y que caracterizan el comportamiento organizacional positivo (Luthans, 2002(Luthans, , 2012. Del mismo modo, desde la Educación Positiva se destaca la infl uencia de los recursos y competencias del profesorado en su rendimiento y en el de su alumnado (Duckworth, Quinn y Seligman, 2009;Lavy, 2020) y se ponen en valor las destrezas que propician el bienestar y la salud del personal laboral en el ámbito educativo (Collie, Malmberg, Martin, Sammons y Morin, 2020;Wang y Hall 2019).…”
unclassified